2016
DOI: 10.1038/srep32592
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Interfacial Dzyaloshinskii-Moriya Interaction from Asymmetric Spin-wave Propagation in W/CoFeB/SiO2 Heterostructures Down to Sub-nanometer CoFeB Thickness

Abstract: Interfacial Dzyaloshinskii-Moriya interaction (IDMI) is important for its roles in stabilizing the skyrmionic lattice as well as soliton-like domain wall motion leading towards new generation spintronic devices. However, achievement and detection of IDMI is often hindered by various spurious effects. Here, we demonstrate the occurrence of IDMI originating primarily from W/CoFeB interface in technologically important W/CoFeB/SiO2 heterostructures using Brillouin light scattering technique. Due to the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 37 publications
7
44
0
Order By: Relevance
“…The first observation of nonreciprocal spin waves [16,68,69] caused by interfacial DMI was achieved by Zakeri et al [70,71] using the spin-polarized electron energy loss (SPEEL) experimental technique. A few years later, nonreciprocal spin waves were observed by means of BLS spectroscopy in several ferromagnet/heavy metal interfaces [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87]. In agreement with the results of Zakeri et al [70,71], these numerous experiments have shown that interfacial DMI creates a noticeable frequency asymmetry in the spin-wave dispersion of counterpropagating Damon-Eshbach (DE) spin waves.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…The first observation of nonreciprocal spin waves [16,68,69] caused by interfacial DMI was achieved by Zakeri et al [70,71] using the spin-polarized electron energy loss (SPEEL) experimental technique. A few years later, nonreciprocal spin waves were observed by means of BLS spectroscopy in several ferromagnet/heavy metal interfaces [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87]. In agreement with the results of Zakeri et al [70,71], these numerous experiments have shown that interfacial DMI creates a noticeable frequency asymmetry in the spin-wave dispersion of counterpropagating Damon-Eshbach (DE) spin waves.…”
Section: Introductionsupporting
confidence: 73%
“…In particular, this numerical technique can be used to calculate the spectrum of spin waves, and when a DMI is present, it reveals different properties characteristic of these systems, such as the spin-wave asymmetry. In this context, simulations have successfully supported theoretical formulations [80,96,97,99,[132][133][134][135][136][137] and experimental measurements [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87]138] on thin-film systems with a homogeneous DMI. A micromagnetic simulation is based on numerically discretizing the continuum description of the magnetic system into a mesh of magnetic moments whose arrangement depends on the discretization method.…”
Section: Micromagnetic Simulations Of Spin Waves With Interfacial Dmimentioning
confidence: 64%
See 1 more Smart Citation
“…3(d the film stacks investigated in this study, M eff is found to be close to the saturation magnetization M s obtained using vibrating sample magnetometer. From this we infer that interface anisotropy is negligibly small in these heterostructures [31]. Fig.…”
Section: A Principle Behind the Determination Of Spin Hall Anglementioning
confidence: 65%
“…Brillouin Light Scattering (BLS) spectra were recorded using a Sandercock-type (3 + 3) pass tandem Fabry-Pérot interferometer and a p -polarized (wavelength of 532 nm with 300 mW power) single longitudinal mode solid state laser. The details of the BLS set up can be found elsewhere 75 . The spectra were recorded in the conventional backscattering geometry at various wave vector orientations selected by mounting the sample on the angle-controlled sample holder providing a range of 10°−60° incident angles corresponding to wave vectors k x lying in the range of 0.004–0.0204 nm −1 .…”
Section: Methodsmentioning
confidence: 99%